2007
DOI: 10.1179/016164107x174156
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen and cerebral physiology

Abstract: Hyperbaric oxygen (HBO) therapy is defined by the Undersea and Hyperbaric Medical Society (UHMS) as a treatment in which a patient intermittingly breathes 100% oxygen under a pressure that is greater than the pressure at sea level [a pressure greater than 1 atmosphere absolute (ATA)]. HBO has been shown to be a potent means to increase the oxygen content of blood and has been advocated for the treatment of various ailments, including air embolism, carbon monoxide poisoning, wound healing and ischemic stroke. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 121 publications
0
53
1
1
Order By: Relevance
“…Hyperbaric oxygen therapy is defined by the Undersea and Hyperbaric Medical Society (UHMS) as a treatment in which a patient intermittingly breathes 760 mmHg oxygen under a pressure that is greater than the pressure at sea level [a pressure greater than 1 atmosphere absolute (ATA)] (Calvert et al, 2007). HBO has been shown to be a potent means to increase the oxygen content of blood and has been advocated for the treatment of various ailments, including air embolism, carbon monoxide poisoning, wound healing, and ischemic stroke (Calvert et al, 2007; Nemoto and Betterman, 2007).…”
Section: Changes Of Oxygen Tension In Brain Tissues During Different mentioning
confidence: 99%
“…Hyperbaric oxygen therapy is defined by the Undersea and Hyperbaric Medical Society (UHMS) as a treatment in which a patient intermittingly breathes 760 mmHg oxygen under a pressure that is greater than the pressure at sea level [a pressure greater than 1 atmosphere absolute (ATA)] (Calvert et al, 2007). HBO has been shown to be a potent means to increase the oxygen content of blood and has been advocated for the treatment of various ailments, including air embolism, carbon monoxide poisoning, wound healing, and ischemic stroke (Calvert et al, 2007; Nemoto and Betterman, 2007).…”
Section: Changes Of Oxygen Tension In Brain Tissues During Different mentioning
confidence: 99%
“…Neuroplasticity -The elevated oxygen concentration in the blood and injured tissue during treatment [136][137][138] can supply the energy needed for neuroplasticity (regeneration of the damaged brain tissue). HBOT induces neuroplasticity by stimulating cell proliferation [139], promotes neurogenesis of endogenous neural stem cells [140], regenerates axonal white matter [141], improves maturation and myelination of injured peripheral and cranial neural fibers [142,143], and stimulates axonal growth thus increasing the ability of neurons to function and communicate with each other [144,145].…”
Section: Hyperbaric Oxygen Therapy (Hbot)mentioning
confidence: 99%
“…Restoration of mitochondrial function -At the cellular level, HBOT can improve cellular metabolism, reduce apoptosis, alleviate oxidative stress and increase levels of neurotrophins and nitric oxide through enhancement of mitochondrial function (in both neurons and glial cells) [146,140,138]. HBOT can restore normal mitochondrial function which is a critical pillar of recovery after TBI [147].…”
Section: Hyperbaric Oxygen Therapy (Hbot)mentioning
confidence: 99%
“…HBO treatment has long been proposed as a commonly available therapeutic schedule to ameliorate AIS-induced brain tissue hypoxia [24] . Previous studies have demonstrated that HBO therapy can enhance the arterial partial pressure of oxygen (PaO 2 ) [25] , increase the oxygen content [26] , stabilize the blood-brain barrier [27] , decrease the intracranial pressure and relieve cerebral edema [27,28] . Some clinical studies [29,30] have justified that intravenous thrombolysis with alteplase, 3-4.5 h after the onset of AIS, may be effective for clinical outcomes.…”
Section: Basic Physiological Effects Of Hbo Therapymentioning
confidence: 99%
“…Previous studies have focused on the effects of HBO on cerebral blood flow, although hyperoxia is associated with the suppression of brain metabolic rate and cerebral blood flow in normal people [94] . Accumulating evidence implicates that HBO therapy significantly ameliorates cerebral blood flow and promotes microcirculation and collateral circulation of ischemic-induced stroke [28,95] . HBO therapy shows a greater positive effect than normobaric oxygen in increasing cerebral blood flow and prompting cerebral metabolism with severe traumatic brain injury patients [96] .…”
Section: Hbo Modulates Cerebral Blood Flow and Brain Metabolismmentioning
confidence: 99%